Do firms behave differently when nominal interest rates are below zero? - Kim Abildgren; Andreas Küchler (Danmarks Nationalbank, 2020)
Yes they do! We examine the case of Denmark - the first country in the world to move its key monetary-policy rate below zero. Using rich microdata and an event-study framework, we find that firms exposed to negative deposit rates to a higher degree than other firms increase their fixed investments and employment - after due control for changes in the level of interest rates. They also tend to rebalance their portfolio of liquid assets away from bank deposits and reduce their degree of leverage. These findings are suggestive of an additional monetary transmission channel operating as nominal interest rates cross zero and become negative. Although we identify a causal effect of facing negative deposit rates, the causal mechanism is more open to interpretation. The transmission channel might imply that firms become more aware of their portfolio composition and alternative opportunities when deposit rates cross zero and become negative.
Keywords: D22; E43; E52; G21; 330; Negative interest rates; Monetary transmission; Firm behavior